A Review of Flipped Classroom Model for Promoting Students’ Basic English Skills - I Kadek Wira Dana; Kerti Nitiasih; Hery Santosa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Twenty-first-century learning has recently become increasingly known and widely applied during the learning process. Considering the learning situation and conditions during this era, where the learning process is carried out online and face-to-face or this is known as blended learning. The use of technology is important during this learning model. Teachers are required to apply learning methods that are appropriate to the current situation. In this review, the flipped classroom model is one of the appropriate learning models to be applied in blended learning in order to promote students’ English basic skills. The present study adopted George’s model (2008) that was adjusted into a qualitative design by Ariantini et al. (2021). The results show that the flipped classroom model can promote students' English basic skills.